A social bot in support of crisis communication: 10-years of @LastQuake experience on Twitter - Bossu, Rémy; Corradini, Marina; Cheny, Jean-Marc; Fallou, Laure (Frontiers in Communication, 2023)
Social media such as Facebook or Twitter are now part of the communication system of many seismological institutes, including the European-Mediterranean Seismological Center. Since 2012 it has been operating a hybrid Twitter system named @LastQuake comprising of a bot for rapid information on global felt earthquakes and their effects, that is complemented by quasi-systematic and rapid answer to users’ questions, especially after damaging earthquakes and earthquake sequences. These exchanges are valued by users and are reported to lower anxiety levels. We present how the different lessons learned over this ten year period drove the development of a new version released in February 2022. Beyond possessing an enhanced hierarchy for the information it publishes, it is also intended to extend its audience and foremost to extend its objectives to the fight against misinformation that often spreads after significant earthquakes, and to the utilization of the teachable moments opened by widely felt non damaging earthquakes to contribute to enhanced earthquake risk awareness and preparedness.